Analysis Comparison Sharia Economy System in Indonesia and Malaysia - Ahmad Firmansyah, Masyekha; Ubaidillah Zubair; Sri Wigati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2024)
The discussion in this journal covers the comparison of sharia economic systems found in Indonesia and Malaysia. The sharia economic system is a system that in its operations it is based on Islamic principles, which include the prohibition of usury (interest) and compliance with Islamic law. This study aims to identify differences and similarities in the implementation of the sharia economic system in the two countries, especially in the banking sphere. This study uses a comparative analysis method between policies and the sharia economic system in Indonesia and Malaysia. The results of this study show that although these two countries uses the same sharia economic system, but there are still differences in regulations And in financial institutions existing sharia on two that country.